2021
DOI: 10.1177/0734242x211021473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bio-medical waste before and during the emergency of novel Coronavirus disease pandemic in India: A gap analysis

Abstract: Considering the widespread transmission of Coronavirus disease (COVID-19) globally, India is also facing the same crisis. As India already has inadequate waste treatment facilities, and the sudden outbreak of the COVID-19 virus has led to significant growth of Bio-medical waste (BMW), consequently safe disposal of a large quantity of waste has become a more serious concern. This study provides a comprehensive assessment of BMW of India before and during the COVID-19 pandemic. Additionally, this article highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Healthcare facilities, such as hospitals, clinics, and medical laboratories, are the region's primary generators of PPE waste ( Sangkham, 2020 ; Maalouf and Maalouf, 2021 ; Rajak et al, 2022 ). The increased use of PPE by healthcare professionals and patients during the pandemic has increased medical waste, including used PPE and face masks.…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare facilities, such as hospitals, clinics, and medical laboratories, are the region's primary generators of PPE waste ( Sangkham, 2020 ; Maalouf and Maalouf, 2021 ; Rajak et al, 2022 ). The increased use of PPE by healthcare professionals and patients during the pandemic has increased medical waste, including used PPE and face masks.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies also show that the volume of medical waste increases rapidly during the COVID-19 pandemic. Research by Rahul Rajak et al, 2021 has shown that India's MW by the COVID-19 pandemic has reached 32,996 tons in only the last 6 months of 2020 [ 29 ]. The study by Olugbemi T Olaniyan et al pointed to the rapid increase in PPE and other biomedical wastes by the COVID-19 pandemic [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Rajak et al (2021), India has generated over 32,996 mt of COVID-19 waste between June and December 2020, of which Maharashtra (789.99 mt/month) is highest average generator of COVID-19 waste, followed by Kerala (459.86 mt/month), Gujarat (434.87 mt/month), Tamil Nadu (427.23 mt/month), Uttar Pradesh (371.39 mt/month), Delhi (358.83 mt/month) and West Bengal (303.15 mt/month). Bhalerao (2021) reported that India generated 56,898.4 tonnes of Covid-19 BMW between June 2020 and June 2021.…”
Section: Present Status Of Biomedical Waste In Indiamentioning
confidence: 99%